THE IMPORTANCE OF RURAL CREDIT IN THE DEVELOPMENT OF DAIRY CATTLE FARMING IN THE MUCURI VALLEY, STATE OF MINAS GERAIS (REMUNOM, 2025)
Dairy farming is one of the essential pillars of agribusiness. The milk production chain is one of the most important socioeconomic activities in Brazil. Produced in almost 98% of Brazilian municipalities, milk is responsible for generating jobs and income for millions of people. In the countryside alone, the gross value of primary milk production is estimated at R$47 billion (MAPA, 2021). In the industrial sector, with the transformation of the raw material milk into its most diverse derivatives, this value generated jumps to R$70.9 billion, corresponding to the net revenue of dairy products, which ranks third in the food industry in Brazil (ABIA, 2020). Thus, given the economic potential of dairy farming, different investment strategies in the sector, such as policies such as rural credit, are essential to subsidize the implementation or expansion of the activity. In this context, development banks stand out in the sector, such as Banco do Nordeste do Brasil, as they implement credit programs with differentiated financing conditions. Thus, to coordinate the entire chain (dairy farming, rural credit and development banks), it is important to develop a simulation of an investment project in dairy farming, through rural credit, and to present the results arising from the financed application.